Sex Differences in a Pink-Collar Occupation - Hunt, Gerald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1993)
The duty of fair representation, counterpart to the power of representation of the certified association, has been studied under three different aspects, namely: its origin, foundation and scope. No attempt has as yet been made, however, to identify and categorize the obligations arising from the duty of fair representation. This article, then, aims at presenting an analytic framework which encompasses the various underlying obligations pertaining to the general interdictions of acting in bad faith or in an arbitrary or discriminatory manner, or of showing serious negligence, as stipulated in section 47.2 of the Quebec Labour Code, and at analyzing the scope of such obligations. General interdictions, as set out in section 47.2 of the Labour Code, are split into two distinct categories of obligations, namely: "obligations which specifically apply to representative duties' and "obligations which pertain to the intensity of such representation".Obligations which specifically apply to representative duties follow from the interdictions of acting in bad faith or in an arbitrary or discriminatory manner. Such obligations differ from "individual responsibilities" which rest with the certified association according to the applicable collective agreement as well as to the grievance which it is called upon to handle, as in the case of formalities with regards to the observance of the internal procedure and of the procedure for grievance arbitration.Obligations which specifically apply to representative duties, as opposed to individual responsibilities, do so indistinctly for the certified association, the salaried employee concerned or the collective agreement on which the grievance is based.The author identifies three types of obligations arising from the interdictions of acting in an arbitrary manner: the obligation to act within the boundaries of the power of representation, the duty to act fairly and the duty to act impartially. The obligation to act within the boundaries of the power of representation prohibits the certified association from refusing to file a grievance, from withdrawing such grievance or from settling it to the detriment of the salaried employee based on grounds conflicting with the collective agreement, on grounds which are extraneous to the dispute, or on a patently erroneous assessment of the basis for the grievance. The duty to act fairly comes into play at various stages of the arbitration procedure. It obliges the association tobe in full knowledge of the facts before it makes decisions in connection with the grievance, and to respect the salaried employee's right to be heard. The duty to act impartially forbids the association from placing itself in a conflict of interest situation with the bargaining unit's salaried employees. The author identifies three cases which are apt to result in the association's being placed in a conflict of interest situation with the salaried employees who are challenging the administrative or disciplinary measure which is being imposed upon them: the association having an internai management problem which opposes it to a salaried employee; the association which allows the employer to participate in its power of representation; the association which participâtes in the management System.The duty to act in a non-discriminatory manner constitutes yet another obligation which specifically relates to representative duties. In this context, the term "discriminatory" is used in a broader sense than that attributed to it by the Charter ofHuman Rights and Freedoms.Clearly, the certified association may not act indiscriminately when it bases its actions on grounds which are discriminatory within the meaning of this law, which prohibits directly acting in a discriminatory manner or acting in a manner which is discriminatory by prejudicial effect. As well, based on inequitable criteria, the association may be unable to distinguish salaried employees' benefits or rights. As opposed to specifie obligations which apply to behaviour, the second category of obligations pertains to the quality of the behaviour rather than to the behaviour itself. Thus, obligations arising out of the interdictions of acting in bad faith or of showing serious negligence, serve to qualify the intensity of the obligations which specifically apply to representative duties, and of individual responsibilities, which rest with the certified association by virtue of the collective agreement. Bad faith refers to malicious, fraudulent, malevolent and hostile behaviour. It worsens the fallure to meet a specific obligation or a particular responsibility. Serious negligence, on the other hand, may be assessed according to the diligence with which the association exercises its power of representation. The author notes that, as a rule, the Labour Court and courts of justice impose an obligation to act diligently with regards to obligations which specifically apply to representative duties. In several cases, however, the mere fact of contravening the specifie obligation constitutes lack of diligence. Nevertheless, the Labour Court and courts of justice adopt different positions when it comes to assessing what constitutes fallure to meet an individual responsibility, as required according to the collective agreement. The Labour Court imposes an obligation to act diligently, whereas courts of justice tend to require proof that acting in bad faith has occurred before deciding upon fallure to meet the duty of representation. In conclusion, the author wishes to emphasize that underlying obligations to the duty of fair representation apply only when the association exercises its power of representation which is conferred upon it by virtue of its certification. In other cases of representation, the association should be bound to fulfil the obligations of the mandatory.